Bone decade actions: are practical results measurable yet? - Alves, Sandra (2012)
Osteoarthritis (OA) has an extremely high disease and economic burden. Despite treatments for OA pain management, data are limited on the adequacy of pain relief in OA patients. SORT will determine the adequacy of pain relief in patients with knee OA and compare patterns of clinical care and outcomes.